OPTIMALISASI INDUSTRI HALAL DI INDONESIA MELALUI PENDEKATAN STRATEGIS DISTINCTIVE COMPETENCE - Irfan Harmoko (Reinforce: Journal of Sharia Management, 2022)
Indonesia is a country that has potential in developing the halal industry. In the State of The Global Islamic Report 2021, Indonesia is in the position of the fourth ranked country in the world. However, in all sectors of the halal industry, Indonesia has not been able to achieve first place. By looking at their distinctive competence, the halal industry in Indonesia can be optimized. This study uses a qualitative phenomenological approach, namely by examining phenomena based on existing data, to be analyzed and interpreted in order to obtain a comprehensive picture of the phenomenon. The results of this study are, Indonesia has distinctive competence in the form of, the number of Indonesian population who are predominantly Muslim, strong regulations that support the halal industry, a variety of cultures and local wisdom, as well as the development of digital technology owned. From this, strategic steps can be drawn up in the form of accelerating the halal certification process in the food, beverage, pharmaceutical and cosmetic sectors, fulfilling the basic needs of Muslim tourists in various tourism places, and involving related parties in increasing socialization and education in the Islamic finance industry sector.